(untitled) (Gestión y Gerencia, 2026)
This article analyzes the implementation and impact of a social service project designed to serve the older adult population in the Loyola Sector, Trinidad Samuel Parish, Torres Municipality, Carora, Lara State, Venezuela. The objective was to promote comprehensive well-being and social integration in this age group through the organization and execution of recreational and playful activities, complemented by personal care and health days. The methodology was based on the Participatory Action Research (PAR) approach, involving diversified upper-secondary education students from the U.E. Colegio Corina de Zubillaga, who conducted a situational diagnosis that identified a high density of elderly individuals and the need for interaction and care spaces. The results showed that recreation, when conceived under the perspective of the Activity Theory originally developed by Vygotsky (1978) and expanded by Leontiev (1978)—which highlights that recreation protects mental and social health through three key reasons: a sense of purpose, social mediation, and internalization and externalization—acts as a protective factor for mental and social health, significantly increasing the perception of well-being, reducing isolation, and strengthening the intergenerational community fabric. The role of community service is discussed as a mechanism to fulfill student social responsibility (Article 13 of the LOE), demonstrating the reciprocity between the educational institution and society. In conclusion, interventions focused on productive leisure and care are essential to validate the autonomy and functionality of older adults in the current Venezuelan context, recommending the institutionalization of these programs.